Nanoimprint lithography: an enabling process for nanofabrication - Zhou, Weimin (Springer Berlin Heidelberg, 2013)
Nanoimprint Lithography: An enabling process for nanofabrication presents a comprehensive description of nanotechnology that is one of the most promising low-cost, high-throughput technologies for manufacturing nanostructures, and an emerging lithography candidates for 22, 16 and 11 nm nodes. It provides the exciting, multidisciplinary field, offering a wide range of topics covering: principles, process, material and application. This book would be of specific interest for researchers and graduate students in the field of nanoscience, nanotechnology and nanofabrication, material, physical, chemical, electric engineering and biology. Dr. Weimin Zhou is an associate professor at Shanghai Nanotechnology Promotion Center, China.